Organic Matter Management in Soils of Semi+Arid and Sub-Humid Regions of India: Problems and Solutions - Anand Swarup (Journal of Soil and Water Conservation, 2022)
Enhancing the long-term sustainable productivity of crops and cropping system is directly related to maintenance of an adequate level of soil organic matter (SOM); a critical component of soil fertility and productivity. The maintenance of SOM in agricultural soils, particularly of semiarid and sub-humid regions on India is generally governed by annual temperature, precipitation and many interacting factors such as soil type, tillage, application of fertilizer, quality and quantity of the residual waste returned to soil, and the method of residues management. Most residues find use as feed and fuel in India and one third of total residues is used as source of organic matter. Application of farmyard manure is the usual practice of Indian farmers. Continuous adoption of the same cropping pattern, unbalanced and inappropriate use of chemical fertilizer, and minimum or no use of organic matter year after year is a major constraints to SOM accumulation. Modifications of cropping sequences need to be explored by introducing legumes in the system for improving SOM accumulation. Alternate land use systems, viz agro-forestry, agro-horticultural and agro-silvi-culture are more remunerative for soil organic matter restoration as compared with sole cropping systems. The constraints for organic matter management in sub-humid and semiarid regions are reviewed, possible solutions are presented and future research needs are outlined.